Inorganic-based drug delivery systems for cancer therapy - Rodrigues, Ana Carolina Félix (2020)
The aging of the worldwide population has associated an increased incidence and prevalence of several pathologies, such as cancer, skin lesions, and neurological disorders. To improve the therapeutic outcome, researchers have been involved in the development of new disruptive therapeutic products that provide personalized and more efficient healthcare solutions. Among them, inorganic nanoparticles such as those made of gold, silica, or graphene-based materials have been used by researchers and clinicians for cancer therapy. Inorganic nanoparticles present unique size- and shape-dependent physicochemical and optical properties that in conjugation with high loading capacities prompted their application as therapeutics, drug delivery vehicles, and imaging agents. Additionally, these structures can also be conjugated with targeting moieties or stealthing agents to further improve their accumulation in the tumor tissue and, consequently, enhance their therapeutic effect. Herein, the advances attained in the application of inorganic nanoparticles in tumor targeting, imaging, photothermal therapy, and delivery of bioactive molecules, such as drugs (e.g., doxorubicin), genetic material (e.g., DNA, siRNA), and immunotherapy mediators are discussed as well as its limitations and toxicity issues.